The law of the single European market : unpacking the premises - Barnard, Catherine; Scott, Joanne (Hart Publishing, 2002)
The evolution of the single market, Paul Craig; pre-emption, harmonisation and the distribution of competence to regulate the internal market, Stephen Weatherill; proportionality and subsidiarity, George Bermann; flexibility in the European single market, Nick Bernard; horizontality, Stefaan Van den Bogaert; enforcing the single market - the judicial harmonisation of national remedies and procedural rules, Michael Dougan; unpacking the concept of discrimination in EC and international trade law, Grainne de Burca; market access and regulatory competition, Catherine Barnard and Simon Deaking; mutual recognition, Kenneth Armstrong; mandatory or imperative requirements in the EU and the WTO, Joanne Scott; the single market, movement of persons and borders, Elspeth Guild; competition policy and the shaping of the single market, Albertina Albors-Llorens; free movement of capital - learning lessons or slipping on spilt milk, Steve Peers; the external dimension of the single market - building (on) the foundations, Marise Cremona.